Antimicrobial and Antibiofilm Activity of Cinnamon (Cinnamomum burmanii) Extract on Periodontal Pathogens—An in vitro study - Panjaitan, Caesary Cloudya; Widyarman, Armelia Sari; Amtha, Rahmi; Astoeti, Tri Erri (European Journal of Dentistry, 2022)
Objective The aim of this study was to analyze the antibiofilm effectiveness of cinnamon (Cinnamomum burmanii) ethanol extract against Porphyromonas gingivalis and Aggregatibacter actinomycetemcomitans in vitro.Material and Methods Phytochemical tests were done to identify the cinnamon extract active substances. Furthermore, a crystal violet biofilm assay was used to analyze biofilm detachment after treatment with different concentrations (15, 10, 7.5, 5, and 2.5%) of cinnamon. Biofilm turbidity was measured at 595-nm wavelength using a microplate reader. Additionally, MTT assay was done to analyze the toxicity level of cinnamon extract on fibroblast cells.Statistical Analysis The obtained data were analyzed for normality using the Kolmogorov–Smirnov test. The differences between each group were analyzed using a one-way analysis of variance statistical test, with a significance level of p <0.05.Results The results showed that the ethanol extract of cinnamon contains active compounds of flavonoids, alkaloids, saponins, tannins, quinones, and terpenoids. MTT result showed the cinnamon extract to be nontoxic. The biofilm assay results showed that all cinnamon concentrations exhibited an antibiofilm effect against P. gingivalis and A. actinomycetemcomitans in all incubation time compared with a negative control (p <0.05).Conclusions Cinnamon extracts were effective in inhibiting biofilm of periodontal pathogens. Cinnamon extract might be useful as an alternative therapy for periodontal diseases. Future studies are still needed to confirm this result in vivo to analyze the efficacy of this extract as mouthwash.
Keywords: cinnamon; biofilm; toxicity; Porphyromonas gingivalis; Aggregatibacter actinomycetemcomitans